High performance computing of explicit schemes for electrofusion jointing process based on message-passing paradigm - Osman, Halijah; Alias, Norma; Sanugi, Bahrom (Universiti Teknologi Malaysia, 2005)
The research focused on heterogeneous cluster workstations comprising of a number of CPUs in single and shared architecture platform. The problem statements under consideration involved one dimensional parabolic equations. The thermal process of electrofusion jointing was also discussed. Numerical schemes of explicit type such as AGE, Brian, and Charlies Methods were employed. The parallelization of these methods were based on the domain decomposition technique. Some parallel performance measurement for these methods were also addressed. Temperature profile of the one dimensional radial model of the electrofusion process were also given.